Eletro-oxidação de efluente contendo nitrogênio amoniacal na presença de cloreto - Brigido, Caroline Rodrigues dos Santos (2017)
The spillage during shipment and disembarkation of fertilizers in Brazilian ports leads to a mixture of fertilizers residues on the pier pavement which are washed by the rain generating a drainage effluent rich in ammoniacal nitrogen and chloride. A sample from the port of Tubarão, Vitória / ES, was used for the tests. The main objective was recovering ammoniacal nitrogen of the sample. In this work two electrolytic cells, with and without Nafion-424 cationic membrane, were tested. In cell (1) was used Ti/Ta2O5- IrO2 anode was used. For cell (2), without cationic membrane, the a Ti/RuO2 anode was used. The removal of ammoniacal nitrogen was higher than 90% and the Chemical Oxygen Demand (COD) higher than 80%, for both sells. These results indicated that tratament is efficient to reduce the concentration of inorganic and organic pollutants presents in the sample. The Ti/RuO2 anode presented better corrosion resistance for saline and acidic environment of the experiment. The cationic membrane, although avoiding the reversibility of the reactions, presented degradation evidences at end of process.